(untitled) (Eurasian Journal of Engineering and Technology, 2023)
Intersections are considered as the most critical elements of the urban roadway network. Although many studies concerned with evaluating and improving intersections in the urban area, so far few have concentrated on the unsignalized intersections, especially three-leg intersections. Therefore, the aim of this paper is to evaluate and improve four three-leg intersections controlled by the STOP sign in different locations in Amman City for the existing and short-term conditions. Highway Capacity Software (HCS-2010) and Synchro-10 software have been used for the evaluation and improvement. While VISSIM-11 software was used for validation and simulation. Evaluation processes using the HCS-2010 and Synchro-10 programs have shown that the left-turn from the minor-street faces high delay and operates in a breakdown traffic condition (Level of Service LOS-F). Warrant-3; (Peak Hour Volume) was applied to determine whether or not the selected intersections are warranted for signalization under existing conditions. The output results showed that three intersections are warranted for signalization and the fourth one is not satisfied. For short-term conditions with a growth of 5.5%, the results of the two-software revealed that the four selected intersections are warranted for traffic signals. The optimum cycle length of traffic signal was selected for each intersection, with two operation modes for the left-turn of the major-street; Protected and Protected-Permitted phase using HCS-2010 and Synchro-10 software and validated using VISSIM-11. The improvements in traffic and geometric conditions resulted in a reduction in vehicular delay with better LOS at the minor approach (LOS-C or LOS-D) as well as the entire selected intersections (LOS-B or LOS-C).